Evaluation for Racial Disparities in Patients Presenting for Sports Medicine Knee Surgery. Issue 7 (31st July 2020) - Wentt, Christa; Jones, Morgan; Strnad, Greg; Briskin, Isaac; Spindler, Kurt; Farrow, Lutul
Objectives: Several clinical studies have outlined differences in clinical outcomes and access to care when controlling for race. No published clinical study has ever investigated healthcare disparities between Black and White patients presenting for sports medicine knee surgery. The purpose of this study is to determine if the racial disparities described in the literature for total joint arthroplasty and spine surgery are also preset in patients presenting for sports medicine knee surgery. Our first hypothesis is that Black patients presenting for sports medicine knee surgery have worse baseline patient-reported quality of life scores, pain, and function compared to White patients. Our second hypothesis is that Black patients have more disease severity at the time of surgery compared to their White counterparts. Methods: We prospectively collected patient-reported outcomes (PROs), disease severity, and treatment utilizing the [BLINDED DATABASE]. Patient race, body mass index (BMI) and insurance were retrospectively collected from the electronic medical record (EMR). We included consecutive patients undergoing both knee arthroscopy (partial meniscectomy) and anterior cruciate ligament (ACL) reconstruction surgery. We excluded patients undergoing other chondral replacement or complex ligamentous procedures (e.g. MPFL reconstruction, multiligamentous knee surgery, etc). Univariate ("unadjusted") analysis was utilized to compare differences between groups with ANOVA, Kruskal Wallis Testing and Pearson's Chi-square testing. Subsequently, a multivariate analysis model was constructed to control for confounding variables within Black patients vs White patients in order to evaluate for racial disparities in baseline PROs and disease severity. All testing was considered significant at the 5% level. Results: We enrolled a total of 4, 557 patients for this study. In the arthroscopy group (APM) we enrolled 3086 total patients. In this group there were 2593 White patients and 408 Black patients. Eighty-five patients identified as "Other". In the ACL reconstruction (ACLR) group there were 1471 patients. In this group 1197 patients identified as White, 202 patients identified as Black and 72 patients identified as "Other". Univariate analysis in the APM group demonstrated racial disparities in certain key metrics. BMI was worse in Black patients (32.4) compared to White patients (30.3) (p < 0.001). Both KOOS pain (41.7 versus 47.2; p < 0.001) and KOOS function (51.5 versus 58.0; p < 0.001) were worse in Black patients compared to White patients. A larger portion of Black patients were current smokers compared to White patients (16.% versus 10%; p < 0.001). Baseline VR12 scores were also lower in Black versus White patients (48.4 versus 55.9, p 0.001). Multivariate analysis revealed no racial disparities for any baseline patient-reported outcome measure (pain, function, or quality of life). This is a result of Black patients being more likely to present with higher BMI, current smoker status, fewer years of formal education, and Medicaid insurance. No significant differences between Black and White patients were noted with respect to disease severity (intraoperative pathology; i.e. worse chondral grade, compartments involved, meniscus tear severity). Our ACLR group demonstrated similar findings on univariate analysis with Black patients more likely to have Medicare/Medicaid than commercial insurance, a higher BMI, smoking history and a lower VR12 score compared to White patients. Linear regression analysis demonstrates that age, gender (female worse), BMI, years of education, smoking status and insurance are all significant drivers of outcome for KOOS pain. With respect to additional intra-articular pathology at the time of ACL tear, female sex and increasing years of education were at an increased odds of having a complete meniscal tear. Neither race or insurance status were significant drivers of concomitant intra-articular findings in ACL tear patients. Conclusions: There is no statistically significant racial disparity in baseline patient reported outcomes with respect to patients presenting for sports medicine knee surgery when controlling for important covariates. Black patients did present with worse subjective KOOS knee pain and functional scores, however, when possible confounding variables were controlled for in a multivariable analysis, there was no difference between the White and Black cohorts. The results of this study show that there may be modifiable risk factors that affect outcomes of patients irrespective of racial background. Addressing factors such as BMI, smoking status and healthcare literacy may help to improve outcomes for patients. Further research into interventions to correct these risk factors is needed.